Avaliação da prevalência de sintomas de ansiedade associados ao trabalho dos peritos médicos da previdência social no Espírito Santo, Brasil - Marchiori, João Guilherme Tavares (2018)
The medical-expert act within the scope of the Brazilian Social Security consists of the medical evaluation of the examinee, to draw a conclusive opinion on the work capacity and characterization of disability for social security and assistance purposes. Forensic decisions inevitably converge on two opposites: concession or refusal. The rejection goes against the interests of the candidates, who can project their disappointment and dissatisfaction on the professional, exposing the latter to potentially stressful situations. Objectives: the present study aimed to evaluate the presence and intensity of occupational stress among Social Security Medical Experts, comparing it to medical experts from other public careers. It also intended to identify the target causal factors, in order to provide organizational managers with essential principles that guide strategies aimed at preserving the mental health of medical specialists. Methods: The evaluation was made through a specific, previously validated job related stress questionnaire and a series of questions about subjectives perceptions on work performance, labor stressors and emotional status. Results: we found overwhelming and alarming prevalence of stress and dissatisfaction related to occupational aspects among social security experts, culminating, in many cases, with emotional exhaustion, characteristic of Burnout Syndrome. Conclusion: there is a high prevalence of job related stress among social security doctors in Brazil, warranting implementation of specific measures in order to ensure the adequate provision of social security services to the population, thus avoiding social injustice and damage to the erary.